Hepatozoon Canis en Colombia - Arcila Quiceno, Victor Hernan; Castellanos Torres, Vilma; Díaz, Sheila; Sánchez, Mónica (Spei Domus, 2005)
The geographical position of Colombia, their climatic conditions make it ideal as a biological niche to a great quantity of agents including the parasitic ones, which have been reported in neighboring countries. This case reports the discovery in canine of the parasite hepatozoon. The Hepatozoon canis was reported first in the India in 1905, and from then on it has been shown to infect dogs in the entire world (Macintire, 1999). The hepatozoonosis is an illness generated by an apicomplexo protozoan blood parasite investigated for the first time in Texas (EE.UU) in 1978 where gametocytes of Hepatozoon was identified in neutrophils circulating of 3 dogs. (Craig et al. 1978). The Hepatozoonosis is an illness transmitted by the Rhipicephalus sanguineus ticks whose distribution is endemic in States united in the states of Texas, Oklahoma and Louisiana; also Brazil, Europe (mediterranean region) Asia ( Japan, Malaysia, Philippines and Middle East) and África.